1985
DOI: 10.1200/jco.1985.3.10.1349
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoembryonic antigen: a useful prognostic marker in small-cell lung cancer.

Abstract: Plasma carcinoembryonic antigen (CEA) was determined in 180 patients with small-cell lung cancer (SCLC) before treatment. An abnormal level (greater than or equal to 6 ng/mL) was found in 34% of patients tested. Patients with extensive disease (39/83) had a significantly higher frequency of abnormal CEA (P = .001) than those with limited disease (22/97). There was a strong correlation between obtaining an objective response--particularly a complete response (P = .00003)--and the absence of an elevated CEA. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
1

Year Published

1988
1988
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 5 publications
1
21
0
1
Order By: Relevance
“…A negative correlation was described between initial high or low levels of NSE and survival (Akoun et al, 1985). Contradictory results have been found for CEA (Sculier et al, 1985, Bucceri et al, 1987, while a normalization of serum AGP level during chemotherapy involved a longer disease-free survival (Ganz et al, 1984). These investigations on tumour markers are based on univariate analysis which limits the conclusions to be drawn.…”
mentioning
confidence: 91%
“…A negative correlation was described between initial high or low levels of NSE and survival (Akoun et al, 1985). Contradictory results have been found for CEA (Sculier et al, 1985, Bucceri et al, 1987, while a normalization of serum AGP level during chemotherapy involved a longer disease-free survival (Ganz et al, 1984). These investigations on tumour markers are based on univariate analysis which limits the conclusions to be drawn.…”
mentioning
confidence: 91%
“…The use of CEA as a prognostic factor has yielded inconclusive results with some studies reporting a relationship between presentation level and survival (Sculier et al, 1985;Laberge et al, 1987;Krischke et al, 1988), although multivariate analyses were not performed and others found no correlation (Lokich, 1982;Waalkes et al, 1982;Jaques et at., 1988), a result confirmed in this study. Studies of serial measurements of CEA have suggested that these correlate closely with the clinical course (Woo et al, 1981;Havemann et al, 1985;Shinkai et al, 1986) although this was not the finding in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Several previous studies have examined the usefulness of CEA as a marker for small cell lung cancer, but as in this case the proportion of patients with elevated levels at presentation has generally been reported as less than half (Goslin et al, 1981;Lokich, 1982;Sculier et al, 1985), limiting its applicability. The use of CEA as a prognostic factor has yielded inconclusive results with some studies reporting a relationship between presentation level and survival (Sculier et al, 1985;Laberge et al, 1987;Krischke et al, 1988), although multivariate analyses were not performed and others found no correlation (Lokich, 1982;Waalkes et al, 1982;Jaques et at., 1988), a result confirmed in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum markers such as NSE (Harding et al, 1990) are related to prognosis but appear to be indicators of mass of disease rather than independent predictors of outcome. The same has been suggested for CEA (Sculier et al, 1985;Laberge et al, 1987) In the present study we have tried to avoid some of these difficulties. The groups of patients have been taken at the extremes of prognosis (survival < 3 months or > 2 years) since, if no difference is detectable, it seems unlikely that one will be detected from a population with a wide distribution of prognosis.…”
Section: Discussionmentioning
confidence: 99%